PENGELOLAAN RETRIBUSI PASAR KECAMATAN - Zukman, M. Refendi; Andri, Seno (Universitas Riau, 2013)
The purpose of this study is to investigateand analyze the factors that affect the management of the market district in Lower RegencyKuantan Kuantan District Singingi. This research was conducted in the District of KuantanKuantan District Downstream Singingi. Where the population and the sample is Head, Departmentof Market, district officials, village and market traders. Data was collected through questionnairedissemination techniques, interviews and observations, once the data is collected and thenanalyzed using qualitative descriptive analysis. The result showed that the management fees thedistrict market in Kuantan District Downstream unfavorable conclusion. The dominant factoraffecting the management of the market district levies are men or human factors.